2022
DOI: 10.3390/ijerph19116586
|View full text |Cite
|
Sign up to set email alerts
|

Observational Variables for Considering a Switch from a Normal to a Dysphagia Diet among Older Adults Requiring Long-Term Care: A One-Year Multicenter Longitudinal Study

Abstract: This one-year multicenter longitudinal study aimed to assess whether older adult residents of long-term care facilities should switch from a normal to a dysphagia diet. Using the results of our previous cross-sectional study as baseline, older adults were subdivided into those who maintained a normal diet and those who switched to a dysphagia diet. The explanatory variables were age, sex, body mass index (BMI), Barthel Index, clinical dementia rating (CDR), and 13 simple and 5 objective oral assessments (remai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…Almost all studies that assessed OD as an oral function in older adults in nursing homes reported only participants who were able to perform OD. 18,19 The cut-off values for older people who could not perform OD were patients classified as level 4 or higher in need of care and degree III or higher in dementia. This study had some limitations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Almost all studies that assessed OD as an oral function in older adults in nursing homes reported only participants who were able to perform OD. 18,19 The cut-off values for older people who could not perform OD were patients classified as level 4 or higher in need of care and degree III or higher in dementia. This study had some limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Although these rates were somewhat higher than the present study results, approximately 30%–50% of older adults in nursing homes are unable to perform OD. Almost all studies that assessed OD as an oral function in older adults in nursing homes reported only participants who were able to perform OD 18,19 …”
Section: Discussionmentioning
confidence: 99%
“…In a previous cross-sectional study, we found that coughing and rinsing were associated with distinguishing between regular and adjusted diets during simple assessments. A longitudinal study [ 8 ] suggested that tongue movement, perioral muscle function, and rinsing could help predict a change from a regular diet to an adjusted diet. Therefore, subjects with poor perioral muscle function and rinsing function are likely to have impaired eating and swallowing functions.…”
Section: Discussionmentioning
confidence: 99%
“…While our prior study included 431 residents who participated in both the 2018 and 2019 surveys, this study examined and analyzed outcomes up to 1 year later for 986 residents who participated in the 2019 survey. There were 394 duplicate residents and 323 residents from nine additional sites in addition to those of the previous study [ 8 ]. Thus, although the data on the subjects analyzed are different, both have significant results for similar endpoints, indicative of the reproducibility and validity of the results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation